2017
DOI: 10.1155/2017/8245345
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Involvement in Radioresistance of Head and Neck Cancer

Abstract: Resistance to the ionizing radiation is a current problem in the treatment and clinical management of various cancers including head and neck cancer. There are several biological and molecular mechanisms described to be responsible for resistance of the tumors to radiotherapy. Among them, the main mechanisms include alterations in intracellular pathways involved in DNA damage and repair, apoptosis, proliferation, and angiogenesis. It has been found that regulation of these complex processes is often controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 74 publications
1
44
0
1
Order By: Relevance
“…Previous studies revealed that a growing number of miRNAs are involved in the radiosensitivity of cancers including NSCLC . In lung cancer cells, overexpression of miR‐133b can sensitize radioresistant lung cancer cells by inhibiting pyruvate kinase isoform M2 (PKM2)‐mediated glycolysis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that a growing number of miRNAs are involved in the radiosensitivity of cancers including NSCLC . In lung cancer cells, overexpression of miR‐133b can sensitize radioresistant lung cancer cells by inhibiting pyruvate kinase isoform M2 (PKM2)‐mediated glycolysis .…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC) is the sixth most common type of cancer worldwide and represents a heterogeneous group of diseases, including several classifications according to the anatomic location, the etiology, as well as molecular features (1,2). The vast majority of HNCs are squamous cell carcinomas (HNSCCs) developing in the oral cavity, the pharynx, or the larynx (2). Etiological factors of HNSCCs development include excessive use of tobacco and alcohol, as well as infection with human papilloma and Epstein-Barr viruses (2).…”
Section: Conclusion: Mir-15b-5p Represents a Potentially Helpful Biommentioning
confidence: 99%
“…The vast majority of HNCs are squamous cell carcinomas (HNSCCs) developing in the oral cavity, the pharynx, or the larynx (2). Etiological factors of HNSCCs development include excessive use of tobacco and alcohol, as well as infection with human papilloma and Epstein-Barr viruses (2). The gold-standard therapy protocol consists of radical surgical resection followed by adjuvant radiotherapy (RT) as monotherapy, followed by chemotherapy or targeted therapy (3).…”
Section: Conclusion: Mir-15b-5p Represents a Potentially Helpful Biommentioning
confidence: 99%
“…A variety of different biomarkers with promising diagnostic, prognostic, and predictive values are currently investigated in head and neck squamous cell carcinoma (HNSCC) . Finished and ongoing clinical trials have been evaluating the potential of reduced‐dose radiotherapy (RT) in less aggressive radiosensitive HNSCC defined by human papillomavirus (HPV) positivity, with the promise of less acute and late toxicity .…”
Section: Introductionmentioning
confidence: 99%